2021
DOI: 10.17533/udea.redin.20210737
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the opening and location ratio on the performance of an H-Darrieus VAWT

Abstract: Vertical axis wind turbines such as Darrieus turbines are a very interesting category of low wind speed domestic wind turbines. Further research work is needed to enhance their efficiency to fulfill the higher demand in small applications for power generation. The main objective of this work is to find a Darrieus turbine design to boost the starting capacity of the turbine through an opening located at the lower surface of the airfoil. We carried out a thorough CFD (Computational Fluid Dynamics) investigation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
(18 reference statements)
0
1
0
Order By: Relevance
“…Based on the computational simulation, a literature review carried out by Plua et al, [12] showed that 80% of the numerical studies were performed in ANSYS software, while the preceding programs are FloEFD and OpenFoam with 6%. ANSYS has been widely used software for similar analyses, such as in spiral chambers, H-Darrieus turbines, and propeller-type turbines [13][14][15]. Moreover, 58% of the researchers used the 𝑘 − 𝜀 turbulence model, followed by the 𝑘 − 𝜔 − 𝑆𝑆𝑇 model with 27% of the application.…”
Section: State Of the Artmentioning
confidence: 99%
“…Based on the computational simulation, a literature review carried out by Plua et al, [12] showed that 80% of the numerical studies were performed in ANSYS software, while the preceding programs are FloEFD and OpenFoam with 6%. ANSYS has been widely used software for similar analyses, such as in spiral chambers, H-Darrieus turbines, and propeller-type turbines [13][14][15]. Moreover, 58% of the researchers used the 𝑘 − 𝜀 turbulence model, followed by the 𝑘 − 𝜔 − 𝑆𝑆𝑇 model with 27% of the application.…”
Section: State Of the Artmentioning
confidence: 99%